Preparation and characterization of bio- and UV- degradable superabsorbent hydrogels based on a novel cross-linker. Issue 1 (2nd January 2020) - Xiao, Yao; Chang, Jinming
ABSTRACT: We prepared bio- and UV-degradable superabsorbent hydrogels based on a novel cross-linker. Fourier transform infrared, thermogravimetric (TG), differential scanning calorimetry (DSC), X-ray diffraction (XRD), and gel permeation chromatography (GPC) were employed to study the properties of the hydrogels. TG, DSC, and XRD data show that our hydrogels are amorphous polymer materials with excellent thermal stability. And they own high absorbency for water and aqueous solutions. Additionally, our superabsorbent hydrogels have good biodegradability and excellent UV degradability according to the GPC data. We suppose the superabsorbent hydrogels have potential applications in many important fields like hygienic products and agriculture due to their high absorbency for aqueous media and good bio- and UV degradability.